EFFEK PERLAKUAN ALKALI NATRIUM HIDROKSIDA TERHADAP KARAKTER FISIS DAN MEKANIS KOMPOSIT SERAT NANAS DENGAN PENGUAT RESIN POLIESTER - Wijianto Wijianto; Ubaidulloh Fatkhul Hami (Inisiasi, 2023)
The use of pineapple fiber is still not optimal and has the potential to be used as a reinforcing material for hybrid composite materials which are expected to get higher composite material strength values. The aim of the research was to determine the dampening effect of NaOH solution on the mechanical and physical properties of pineapple fibrous composites. The research was conducted during the day at the Muhammadiyah University of Semarang (UNIMUS). The research stage is making test samples with molds according to ASTM D638 and ASTM D790 standards by pouring using Yukalac BQTN Polyester Resin. The resulting mold is then mixed with a catalyst and the pineapple fiber is applied in random directions. Tests are carried out mechanically, namely tensile and bending. The test results were then taken with macro photos. The NaOH solution concentration was given starting from 0%, 5%, 10%, and 15% with soaking for 24 hours. The results of the research were that the tensile test produced the largest tensile strength value for the 10% concentration specimen at 24.20 Mpa, while the largest elastic modulus value at the 5% concentration was 415.467 Mpa. In the flexural test, the highest value was produced for the 5% concentration specimen at 1.09 Mpa and the highest elastic modulus value at the 15% concentration was 16,350 Mpa.